Gender-specific negative association between serum vitamin B12 and testosterone levels in females: the modifying role of BMI in a US adult population - Zhao, Xin; Lyu, Xiaohong; Wang, Hai; Li, Yanan; Peng, Fei; Zhang, Yushi (Frontiers in Nutrition, 2025)
BackgroundAn increasing number of studies have highlighted the potential role of vitamin B12 in hormonal health, especially its relationship with testosterone levels. Nevertheless, studies examining the association between vitamin B12 and testosterone, particularly in the general population and among women, remain scarce. Using data from National Health and Nutrition Examination Survey (NHANES) 2011–2014, this study aimed to investigate the relationship between vitamin B12 and testosterone levels.MethodData for this study were obtained from the NHANES conducted between 2011 and 2014. Multivariable linear regression models were employed to evaluate the associations between vitamin B12 levels and testosterone concentrations in adult participants.ResultsThe final study cohort consisted of 4,571 participants with a mean age of 48 ± 18 years. Among them, 50.8% were male, and 49.2% were female. Multivariable weighted linear regression revealed a significant inverse association between serum vitamin B12 levels and testosterone concentrations in females. This association was observed across all three models, including the unadjusted model (β = −0.010, 95% CI -0.016 to −0.005), adjusted model I (β = −0.007, 95% CI -0.013 to −0.002), and adjusted model II (β = −0.008, 95% CI -0.014 to −0.002). Additionally, body mass index (BMI) was identified as an effect modifier, demonstrating a significant negative interaction (β = −0.021, 95% CI -0.032 to −0.010) between serum vitamin B12 and testosterone in women aged 20 to 39 years. No statistically significant associations were found between serum vitamin B12 concentrations and total testosterone levels in either the male population or the overall population.ConclusionThis study demonstrated that serum vitamin B12 levels were negatively associated with testosterone concentrations in the female population, whereas no significant association was observed in males. Moreover, BMI was found to significantly influence the relationship between vitamin B12 and testosterone levels.